Olga : a novel - Schlink, Bernhard (HarperVia, an imprint of HarperCollinsPublishers, 2021)
"Abandoned by her parents, Olga is raised by her grandmother in a Prussian village around the turn of the 20th century. Smart and precocious, endearing but uncompromising, she fights against the prejudices of the time to find her place in a world that sees women as second-best. When Olga falls in love with Herbert, a local aristocrat obsessed with gaining all the power, glory and greatness the modern age can provide, her life is irremediably changed. Their love goes against all odds and encounters many obstacles, entwined with the twisting paths of German history, leading us from the late 19th to the early 21st century, from Germany to Africa and the Arctic, from the Baltic Sea to the German south-west. Unfolding across centuries, Olga is an epic romance, and a wrenching tale of devotion to a restless man in a fateful moment of great rebellion. Though Olga lives her life within the margins of others, her magnetic presence breathes vivid life into these pages. Told in three distinct parts-which brilliantly shift from different points of view to the epistolary form-Schlink paints a full portrait of a singular woman's complex life"--